Evaluating the Effects of 60°C Heating for 90 Min on Bacterial Pathogen Viability and IgG Concentration in Bovine Colostrum - Mostafa Moazeni; Aria Rasooli; Mohammad Nouri; Masoud Ghorbanpoor; Nader Mosavari; Amir Zakian (Veterinary Medicine and Science)
ABSTRACT The purpose of this study was to investigate the effects of heat treatment on bovine colostrum at 60°C for 90 min on the viability of bacterial pathogens and IgG concentration. In the first experiment, eight batches (4.5 L) of bovine colostrum were inoculated with Escherichia coli (106 cfu/mL), Salmonella Enteritidis (106 cfu/mL), Mycobacterium avium subsp. paratuberculosis (MAP;103 cfu/mL) and Mycobacterium avium subsp. avium (MAA;103 cfu/mL). These batches were then heat‐treated using a commercial on‐farm batch pasteurization system at 60°C for 90 min. Samples were collected before inoculation, after inoculation, and at 30, 60, 75 and 90 min post‐heat treatment to assess pathogen viability. In the second experiment, batches of colostrum (10 L) were heated at 60°C for 90 min across seven replicates. Subsamples were collected before treatment and at 30, 60, 75 and 90 min during heat treatment to measure IgG concentration. The findings indicated that heating colostrum at 60°C for 30 min resulted in detectability (viability) of E. coli and S. Enteritidis in 12.5% and 25% of replicates, respectively, and after 60 min in 0% of replicates. In addition, heat treatment at 60°C resulted in the growth of MAP and MAA in 25% and 12.5% of replicates after 60 min, respectively, and 0% of replicates after 90 min. Importantly, the treatment did not significantly affect IgG concentration (5.7 mg/mL reduction after 90 min) (p > 0.05). According to the results, heating colostrum at 60°C for 60 min completely eliminates E. coli and S. Enteritidis and can render mycobacteria undetectable by culture in most situations. In situations where the control and eradication program for Johne's disease is being considered, heat treatment of colostrum at 60°C for 90 min can be beneficial without concern for a significant reduction in IgG levels.